Penggunaan Bahasa Ambigu pada Teks Bacaan Lembar Kerja Siswa (LKS) Master Mata Pelajaran Bahasa Indonesia untuk SMP/MTS Kelas VIII - Lestari, Fitri; , Drs. Yakub Nasucha, M.Hum (2017)
The purpose of this study is to classify the types of ambiguity, describing the causes of ambiguity, and analyze the meaning contained of words, phrases and sentences that are ambiguous. This type of research is descriptive qualitative, with the object of research is LKS Indonesian Master Lesson for SMP/MTs Class VIII. Data collection technique used see and record. Data analysis technique used is grouping data, analyze and conclude. While the validity of the data using a technique intrarater and interater The results obtained show that there are three forms of ambiguity/ambiguity of meaning, namely ambiguity phonetic, grammatical and lexical. Phonetic ambiguity due to the addition of phonemes and the lack of lag when a word is spoken. The intermingling of language sounds resulted obscurity of meaning so that it becomes ambiguous. Grammatical ambiguity at the level of words occur because of lack of accessory words, causing the sentence becomes ambiguous and illogical. While in the third ambiguity lexical ambiguity occurs because of lack context of the sentence. Keywords: ambiguity, text reading worksheets.